Pengaruh Kinerja Lingkungan, Pengungkapan Emisi Karbon, dan Board Gender Diversity terhadap Nilai Perusahaan - Alisha Ardiningrum; Muhammad Yusuf; Gentiga Muhammad Zairin (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study examines the effect of environmental performance, carbon emission disclosure, and board gender diversity on firm value. A quantitative approach was employed using secondary data from annual reports, sustainability reports, and stock price data of energy, basic materials, and industrial companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. Panel data regression analysis was conducted using EViews 13. The results show that environmental performance and board gender diversity have no significant effect on firm value, while carbon emission disclosure has a negative and significant effect. These findings indicate that investors have not considered environmental performance and board gender diversity as primary investment factors, whereas carbon emission disclosure is perceived as a signal of regulatory risk and energy transition costs that reduce firm value. The study is limited by sector coverage, observation period, and variable proxies. Future research should expand the sample, observation period, and environmental measurement standards.